Formation of reflection in the process of independent educational and cognitive activity of students (Pedagogy of Higher and Secondary Education, 2022)
The notion of reflextion has been more exact: components, criteria, exponents and levels have been illuminated as components of a model’s structure of pedagogical university student’s reflextion forming in the process of self-dependent learning activity.
Keywords: reflextion; structure of reflextion; criteria and exponents reflextion; model of reflection formimg; reflextion-oriented situations; self-dependent learning activity